A cone-beam computed tomography study to assess anterior loop and other anatomic variations in mental foramen area in an Iranian population - Leila Khojastepour; Sahar Assar; Najmeh Movahhedian; Mohammad Mahjoori-ghasrodashti; Farzaneh Ahrari (Universidad de Concepción., 2022)
Purpose: This study aimed to determine the prevalence and length of the anterior loop (AL) of the inferior alveolar nerve, and evaluate the emergence direction of the mental nerve and the location of mental foramen in a group of Iranian patients. Material and Methods: This study was carried out on CBCT scans of 150 patients (57 males and 93 females; mean age 40.8 ±14.33 years). The presence and extent of the AL was determined in reconstructed images. The emergence path of the mental nerve was classified into three groups: anteriorly directed emergence, right-angled pattern of emergence, and posteriorly directed emergence. The location of mental foramen relative to adjacent premolars was determined. Results: AL was identified in 14.7% of the cases with a mean length of 1.39± 0.91 mm (range 0.25 to 3.50 mm). No significant differences were observed in the prevalence and extent of the AL between genders (p>0.05). The right-angled pattern of emergence was more dominant (43.7%). The most prevalent location of mental foramen was between the first and second premolars (68.3%). There was no significant association between the presence of AL with the path of emergence of the mental nerve (p=0.627) or the location of the mental foramen (p=0.100). Conclusion: The prevalence of anterior loop was relatively low in the present sample (14.7%) with a length range of 0.25 to 3.5 mm. Due to the importance of this anatomic variation in implant surgery, it is suggested to carefully assess CBCT images before the surgical procedure to avoid neurosensory complications.